Learning mathematics using fun-math application for pre-school / Abdul Hasib Sadiqin Adam Shukri … [et al.] - Adam Shukri, Abdul Hasib Sadiqin; Musa, Madiawati; Amir, Aimi Liyana; Mohd Salleh, Nurhashikin; Zulkifli, Norlindamalia (UiTM Cawangan Melaka Kampus Jasin, 2021)
Education in the 21st century is characterized by: user-centeredness, on-demand provision and delivery, engagement of learners, and technology-mediated teaching and learning. Nowadays, the increasing of the game application is uncontrollable. Kids tend not to study and just want to play games. Most of them like to play games because the games are more interesting compared to books. Kids not attracted with traditional studies (books) and easily lose focus during the study. Mathematics syllabus at the primary school is formally and theoretically, and very book-based learning. Mathematics subject is not interesting for children, because it is a serious topic that cannot be learned in a relaxed situation like playing games. Primary school students at the age of seven to nine years old learn addition, subtraction, multiplication, division and fractions will hardly understand mathematics, and they assume that mathematics is very difficult to learn if the teacher does not know on how to attract and promote fun learning to students. With the aid of instructional technology, digital devices and advancement of educational mathematics games, teachers can use it in the learning process in the classroom. Since educational mathematics game has gained considerable interest in education circles due to its capability of enhancing the learning process among students, the teachers need to have their criteria and set goals in order to achieve the desired learning outcomes.